Investigation of zonal velocity of equatorial plasma bubbles (EPBs) by using GPS data. (May 2017) - Sarudin, I; Hamid, N S A; Abdullah, M; Buhari, S M
Abstract: The zonal velocity of equatorial plasma bubbles (EPBs) have been studied using various techniques in the past few years. However, the derivation of the zonal drift of EPBs using GPS ROTI have not been studied before. This study aims to investigate the zonal drifts of EPBs using GPS ROTI keogram. The Malaysia Real–Time Kinematic GNSS Network (MyRTKnet) which consists of 78 GPS receivers was used to study the occurrence of EPBs along 96°E - 120°E longitude. The EPBs are detected from daily ROTI keogram that derived from east-west cross section of two dimension of ROTI maps at 5°N for every 5 minutes. On the night of 29 March 2011, 10 consecutive EPBs with periodic spacing between 50 km to 100 km were recorded by MyRTKnet. In this study, we obtained that highest drift velocity is about 277.7 m s-1 at 1400 UT which denoted by EPB 7 whereas the lowest drift velocity is EPB 4 with 27.8 m s-1 at 1600 UT. Besides, the EPBs are propagated towards the east from 200 km to 2800 km with average velocities is about 55.6 m s-1 to 138.9 m s-1.